Healing Through Support: A Descriptive Study on Social Support for Bullying Victims in Junior High School - Dinda Nur Rahmadhani; Rulita Hendriyani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Bullying is a form of violence that frequently occurs in school environments and poses a serious challenge for junior high school or Islamic junior high school (MTs) students, particularly during early adolescence, a stage characterized by identity exploration. The impact of bullying can affect various aspects of victims’ lives, including psychological, social, physical, and academic domains. This study aims to describe the level of social support received by MTs students who have experienced bullying. The study employed a descriptive quantitative approach with 90 adolescent respondents aged 12–16 years. The instruments used were the Olweus Bully/Victim Questionnaire (OBVQ), which demonstrated a reliability coefficient of 0.893 and item validity ranging from 0.340 to 0.673, and the Child and Adolescent Social Support Scale (CASSS), which showed an alpha reliability above 0.962 and item validity greater than 0.30. The findings revealed that most students reported a moderate level of social support (34.4%), while most of the bullying victims also fall into the moderate category (36.7%). These results indicate that although most students receive a sufficient level of social support, some still experience low levels of support, which may exacerbate the negative effects of bullying. Therefore, this study highlights the importance of strengthening social support systems within religious-based school environments as a preventive and intervention strategy for bullying victims.Bullying merupakan bentuk kekerasan yang kerap terjadi di lingkungan sekolah dan menjadi tantangan serius bagi siswa SMP/MTs, terutama pada masa remaja awal yang ditandai oleh pencarian jati diri. Dampak dari bullying dapat memengaruhi aspek psikologis, sosial, fisik, dan akademik korban. Penelitian ini bertujuan untuk menggambarkan tingkat dukungan sosial yang diterima oleh siswa MTs yang menjadi korban bullying. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan responden sebanyak 90 remaja berusia 12–16 tahun. Instrumen yang digunakan yaitu Olweus Bully/Victim Questionnaire (OBVQ) dengan reliabilitas sebesar 0,893 dan validitas item antara 0,340–0,673, serta Child and Adolescent Social Support Scale (CASSS) dengan reliabilitas alpha di atas 0,962 dan validitas item > 0,30. Hasil analisis menunjukkan bahwa sebagian besar siswa mengalami dukungan sosial pada kategori sedang (34.4%) dan yang menjadi korban bullying juga pada kategori sedang (36.7%). Temuan ini menunjukkan bahwa meskipun sebagian besar siswa merasakan dukungan sosial yang cukup, masih ada sebagian yang berada dalam kondisi minim dukungan, yang berpotensi memperparah dampak negatif bullying. Penelitian ini menegaskan pentingnya penguatan sistem dukungan sosial di lingkungan sekolah berbasis agama sebagai langkah preventif dan intervensi terhadap korban bullying.